Pengaruh Penerapan Teknologi dalam Sistem Informasi Akuntansi dan Pengendalian Internal terhadap Kualitas Laporan Keuangan : (Studi Empiris: pada PT. Kimia Farma Apotek Unit Bisnis Daerah) - Muhamad Apep Mustofa; Najibullah Najibullah (Jurnal Neraca Peradaban, 2021)
The quality of the financial statements is the basis for being able to assess the company's financial position, so that from the results of the analysis the interested parties make a decision. Accounting Information Systems are very helpful in preparing financial reports, but in the process there needs to be a control system and must understand the business flow so that appropriate and quality financial reports are formed. Based on the results of the f test, it is known that the significance value for the effect of X1 and X2 simultaneously on Y is equal to 0.000 <0.05 and the F value is 24.784> F table 3.06, so it can be concluded that there is an influence between the Accounting Information System and internal control with quality. Financial statements, which means that there is an effect of the independent variable X1 and the independent variable X2 simultaneously on variable Y.